Killing the Black Body: Necropolitics and Racial Hierarchies in Digital Gaming - Gray, Kishonna L. (Filozofski vestnik, 2023)
The purpose of this essay is to explore the patterns of antiblackness within contemporary gaming. Video games are sites of necropolitical logics that use Black death to propel narratives. But even more concerning, is that these games might make sense of larger desires of white colonial supremacy, attempting to remove and destroy its troubled racialized past. Ethnographic observations also engage gaming as a carceral logic that seeks to surveil, police, and criminal Blackness. Under these conditions, it is imperative to explore how the continuation of the institution of slavery within policing is actively embedded into technical and digital practices, leading to carceral conditions for those subject to its power and gaming provides a pathway to engage this trend.